Towards a digital twin based decision support system for the context-based dynamic configuration of hybrid cyber-physical production systems - Meliadis, Panagiotis (Stellenbosch : Stellenbosch University, 2023)
Thesis (MEng) -- Stellenbosch University, 2023.